Turbulence in the atmospheric boundary layer: intercomparison among Arctic stations, deviations from MOST, and submeso motions - Schiavon, Mario <1986> (Alma Mater Studiorum - Università di Bologna, 2020)
Monin–Obukhov similarity theory (MOST) applicability is limited in several conditions: e.g., weak wind and very-stable stratification; complex terrain; presence of non-local, submeso motions. In this work, two years of observations from three Arctic stations are considered, to characterize the near-surface turbulence exchange in the area, which presents critical conditions for MOST applicability: i.e., complex terrain and long-lasting stable conditions, which favour submeso motions like gravity waves. Particular attention is dedicated to the similarity relationship between the shear stress, τ , and the vertical velocity variance, <w^2>, which are key variables to characterize the vertical turbulence exchange. Besides the stability effect predicted by MOST and the topographic influence, the effect of submeso motions on the τ /<w^2> similarity relationship is considered. This is done by using spectral analysis and by defining a parameter,R_τ , which quantifies the relative low-frequency contribution to the shear stress, and thus the strength of the submeso effect. It is shown that submeso motions affect small-scale turbulence thus modifying the flux-variance similarity relationship, which, besides stability and surface characteristics, depends on R_τ . In particular, the efficiency of the vertical transport by small-scale turbulence (i.e., τ /<w^2>) diminishes for increasing submeso effect (i.e., increasing R_τ ). This connects MOST applicability with more profound characteristics of the turbulent flow—i.e., the different time scales of the flow and the interplay among them. Results has impacts on modelling closures. In particular, considering the budget of (i.e., the stream-wise component of the shear stress), a simple balance among shear production, buoyancy, and pressure redistribution does not hold when the submeso effect is significant (i.e., R_τ>>1). This demands for a modification of the closures and/or for an extension of the budget, with additional terms accounting for ...